Comparative Long-Term Evaluation of Patients With Juvenile Inflammatory Myopathies. Issue 1 (September 2016) - Elahi, Hafiz A.; Bertorini, Tulio E.; Igarashi, Masanori; Mays, William H.; Whitaker, John N.
Abstract: Objectives: We conducted a retrospective study analyzing the clinical features, laboratory findings, demographics, and long-term prognoses of patients with juvenile inflammatory myopathies to determine possible predictors indicating the use of aggressive immunotherapy and the response to and complications of treatment. Methods: The medical records of 41 patients with juvenile inflammatory myopathies seen at University of Tennessee–affiliated hospitals in Memphis from 1969 to 2008 were evaluated. Patients' clinical characteristics, laboratory studies, muscle biopsies, and electromyography were reviewed. All patients were treated with prednisone initially; additionally, 14 patients received varying combinations of other immunosuppressant therapies. Results: Seventy-three percent of the patients experienced remission. Patients in the group that did not go into remission had specific characteristics at onset: they were comparatively older and had more severe rashes, contractures, arthritis, and systemic involvement. Also, patients with positive autoantibodies (antinuclear antibody, rheumatoid arthritis factor) had better outcomes. Conclusions: Juvenile inflammatory myopathies have relatively good prognoses. Initial presentation at advanced age or with severe rash, systemic vasculopathies, anemia, or arthritis portends refractory disease; in these patients, second- and third-line therapies improve outcome.